Hubungan Antara Regulasi Emosi Dengan KesejahteraanSubjektif Pada Remaja - RINI, OKTAFIYANA KUSUMA (2016)
This research aimed at examining the correlation between the emotional regulation and the subjective welfare in teenagers. The early hypothesis proposed in this research was that there was a positive correlation between the emotional regulation and the subjective welfare in the teenagers. The higher the emotional regulation, the higher the subjective welfare in the teenagers would be. In contrary, the lower the emotional regulation, the lower the subjective welfare in the teenagers would be. The subjects in this research were the students of class XII of SMA Negeri 1 Wonosari Klaten. The technique of sampling used was the method of cluster sampling, from all classes XII, the researcher drew at random and obtained samples of class XII IPA 1, XII IPA 4, XII IPS 3. The scales used were the scale of emotional regulation and the scale of subjective welfare. The technique of data analysis used in this research was the technique of the Pearson product moment correlation to test the correlation between the emotional regulation and the subjective welfare in the teenagers. The Pearson product moment correlation showed coefficient as much as 0.350 with p = 0.001 (p < 0.005) that meant that there was a positively significant correlation between the emotional regulation and the subjective welfare of the teenagers. Therefore, the hypothesis of the research was accepted. Coefficient of the determination (r²) was as much as 0.123, therefore, the contribution of the emotional regulation on the subjective welfare was as much as 12.3%. The level of the teenagers' emotional regulation was categorized as moderate with the empirical mean was as much as 52.12 and the hypothetical mean was as much as 45 which were in the range of 39 ≤ x < 51. Then, the variable of subjective welfare had the empirical mean as much as 42.07 and the hypothetical mean as much as 36 ranging from 31,2 ≤ x < 48 that meant that the subjective welfare in the teenagers was categorized as moderate.